Emergency room pain relief - Nature Research (16552612) (2015)
A transbuccal tablet containing a low dose of fentanyl is as effective as standard opioid therapy for pain relief in the emergency department, according to the results of a double-blind placebo-controlled clinical trial published in the Journal of Emergency Medicine, Trauma and Acute Care . Providing timely and adequate pain relief is an important goal for doctors working in emergency departments, but many patients still feel undertreated, a phenomenon referred to as oligoanalgesia. Inadequate pain relief occurs for various reasons, including the lack of a registered nurse, inability to gain intravenous access, or delays in placing intravenous catheters to administer the painkillers. Stephen Thomas of the Hamad Medical Corporation in Doha and his colleagues recruited 50 patients in Qatar with isolated orthopaedic injuries that do not involve a fracture but are painful enough to warrant opioid analgesia. He then gathered their demographic data and randomly divided them into two groups. Patients in one group were given standard opioid therapy consisting of two orally ingested tablets, each containing 5 mg oxycodone and 325 mg acetaminophen and a comparable tablet with no analgesic effect. Those in the other received two placebo tablets and a single 200 μg dose of the opioid fentanyl delivered orally. They found very few differences between the two groups. Patients in both experienced a significant reduction in pain within 10 minutes of the analgesic drugs being administered. None reported significant side effects and more than three quarters of the patients in each arm also reported that they would want to be given the same medication again in the event of episodes of similar pain in the future. The researchers suggest that a 200 μg dose of fentanyl should be considered as being roughly equivalent to a combination of 5 mg oxycodone and 325 mg acetaminophen, but emphasize that the small sample size and the subjective measures of pain intensity used in the study make the results inconclusive. Nevertheless, the findings warrant further investigation into the potential role of fentanyl in emergency departments, which are facing increasing demands owing to larger numbers of patients. “The potential utility of fentanyl is its rapid onset and ease of use in patients via the oral transbuccal route,” says Thomas. “The follow-up plan is use of transbuccal fentanyl here at the Hamad General Hospital emergency department. This will occur as part of a carefully monitored trial only after the ethics board approval.” Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0